PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA PENGGUNA KENDARAAN RANMOR DINAS R2 DAN R4 PADA PUSLITBANG POLRI BERBASIS JAVA: PENDAHULUAN ; METODE : HASIL ; KESIMPULAN ; DAFTAR PUSTAKA. - Muhammad Rizki Akbar (Jurnal Litbang Polri, 2023)
ABSTRACT This study aims to find out what factors influence the use of vehicle data collection applications at the National Police Research and Development Agency, in addition to providing information about official vehicle data, it will also make it easier for employees in charge of managing logistics, especially for official vehicles, which are very large in number. using quantitative methods. the data collected is secondary data, with observation techniques, interviews and data validation. through direct observation see further problems in the field. from the results of this study it can be concluded, with this data collection system the data processing process becomes easier, more accurate and saves time. This data collection application includes the identity of the owner, vehicle number, brand, etc., another advantage is being able to print vehicle user reports with a timeframe in real time, so that data accuracy can be guaranteed and minimize the occurrence of duplicate data. Keywords: respondents, data collection, accuracy Keywords : real time, data collection, accuracy